2014
DOI: 10.1186/s40200-014-0116-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic activity of different oils through their effect on arylsulfatases

Abstract: BackgroundDiabetes mellitus (DM) is characterized by the overproduction of the reactive oxygen species which affects the integrity of the lysosomal membrane affecting lysosomal enzymes. The effect of these species is blocked by some natural products as antioxidants. In the current study, groups of normal and streptozotocin (STZ)-induced diabetic rats were treated by Nigella sativa (NS), olive and canola oils and subjected to the study of arylsulfatases as a model of lysosomal enzymes. The aim of the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Some studies revealed that the extract of N. sativa seeds increases glucose-induced insulin release in isolated Langerhans islets from rats ( 16 ). Some other studies also have suggested anti-diabetic effects of N. sativa and thymoquinone ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 90%
“…Some studies revealed that the extract of N. sativa seeds increases glucose-induced insulin release in isolated Langerhans islets from rats ( 16 ). Some other studies also have suggested anti-diabetic effects of N. sativa and thymoquinone ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 90%
“…Olive oils have demonstrated, in animal studies, a strong capacity to improve blood glucose concentration and diabetic complications at the enzymatic level, their mechanism of action being assigned to their antioxidant activity [ 170 ]. Moreover, this fact has been supported by the capacity of bioactive compounds of olive oil to inhibit the gluconeogenesis pathways in liver, as a result of the inhibition of glucose-6-phosphatese enzyme, besides the capacity to induce a significant enhancement in the hepatic catalase activity in vivo [ 200 ]. In the same way, Al-Azzawie and Alhamdani [ 162 ] demonstrated the capacity of the long-term intake (16 weeks) of oleuropein to restore glucose blood levels in diabetic rabbits [ 162 ].…”
Section: Biological Activity Of Olive Oil Compounds: In Vitro and mentioning
confidence: 99%
“…The disturbances of its homeostasis seem to be associated not only with diabetes, but also with others [ 4 ]. Recently, it was reported that the lysosomal enzymes arylsulfatases were significantly changed in experimental diabetes [ 5 ]. In fact, the treatment of diabetes through food sources is valuable around the world.…”
Section: Dear Editor;mentioning
confidence: 99%